Stress Inversion of Coal with a Gas Drilling Borehole and the Law of Crack Propagation - Tianjun Zhang; Lei Zhang; Shugang Li; Jialei Liu; Hongyu Pan; Shuang Song (Energies, 2017)
For studying the law of crack propagation around a gas drilling borehole, an experimental study about coal with a cavity under uniaxial compression was carried out, with the digital speckle correlation method capturing the images of coal failure. A sequence of coal failure images and the full-field strain of failure were obtained. The strain softening characteristic was shown by the curve. A method of curve dividing—named fitting-damaging—was proposed, combining the least square fitting residual norm and damage fraction. By this method, the five stages and four key points of a stress-strain curve were defined. Then, the full-field stress was inverted by means of the theory of elasticity and the adjacent element weight sharing model. The results show that σci was 30.28–41.71 percent of σf and σcd was 83.08–87.34 percent of σf, calculated by the fitting-damaging method, agreeing with former research. The results of stress inversion showed that under a low stress level (0.15 σf < σ < 0.5 σf), microdamage evolving into plastic failure later was formed around the cavity. Under a high stress level (0.5 σf < σ < 0.85 σf), the region of stress concentration suddenly crazed and formed a brittle crack. When σ ≥ 0.85 σf, the crack was developing, crack lines were connecting with each other, and the coal finally failed. The outcome of the stress inversion was completely concomitant with the images of crack propagation. Additionally, the stress around the cavity was able to be calculated accurately.